Genetic analysis of homologous recombination repair of DNA double-strand breaks in Drosophila melanogaster. - Thomas, Adam. (2017)
Abstract: Eukaryotic cells employ a number of pathways to ensure that their genomes are faithfully duplicated and accurately repaired when damaged. One critical pathway for the repair of DNA double strand breaks (DSBs) is homologous recombination (HR). HR involves copying DNA sequence from an intact template, often a sister chromatid, to restore genetic information lost at a DSB site. The HR pathway is dependent on many proteins, including BRCA2, RAD51, HELQ and BLM. Mutations in these and other repair proteins result in an increased risk for various cancers, but their molecular mechanisms are not completely understood. We have used Drosophila melanogaster to investigate various aspects of HR using a genetic approach. First, we confirmed that Drosophila Brca2 and Rad51 are equally important in the repair of DSBs induced by transposon excision, mutagenic chemicals or radiation. This is consistent with the established role for Brca2 in recruiting Rad51 to the sites of DSBs. Unlike its mammalian homologs, DmBrca2 does not have a Rad51-independent role in mitotic DSB repair. We went on to show that brca2 mutants in flies are sensitive to the topoisomerase inhibitor, camptothecin. This sensitivity is exacerbated by mutations in the cytochrome P450 gene, Cyp6d2. We showed that cyp6d2 mutations are widespread in Drosophila stocks, which can skew results from experiments using this drug to investigate DNA repair mechanisms. We rescued the sensitivity phenotype using a wild type copy of Cyp6d2. We also looked at the steps of HR downstream of Rad51 recruitment. We showed that DmHelQ and DmBlm are both involved in promoting accurate HR repair of a DSB. In the absence of either or both of these enzymes, we see a decrease in the frequency and efficiency of accurate repair along with a compensatory increase in inaccurate repair processes. We suggest a model to explain these observations. Together, our data have clarified several intermediate steps of homologous recombination repair of a DSB. This dissertation illustrates the effectiveness of using Drosophila melanogaster to study DNA repair mechanisms.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Biology.; Advisor: Mitch McVey.; Committee: Catherine Freudenreich, Sergei Mirkin, Susan Ernst, and Michael Brodsky.; Keyword: Biology.